Zasoby rodziny a umiejętności szkolne dzieci 6- i 7-letnich - Kaczan, Radosław; Rycielski, Piotr (Wydawnictwo Naukowe UAM, 2013)
The research describes the relationships between family resources and skills necessary for learning mathematics, reading and writing. Family recourses are defi ned as parents’ education background, the number of books and the material wealth of the household. The research was carried out on a national representative random sample of 6- and 7-year-old children (N = 3029). The School-Entry Skills Test (TUNSS) and the parental questionnaire were applied during the study. The level of education of the mother and father is shown to have the strongest impact on the child’s skill level. The variables describing the material status of the family had a relatively strong impact.
Family resources and academic skills of 6- and 7-year-olds
Keywords: academic skills; early school age; social capital; socio-economic status